Designing an academic support and development programme to combat attrition among non-traditional medical undergraduates - Moagi-Jama, Mpho Priscilla (University of the Free State, 2009)
The overall aim of this study was to design an integrated and holistic programme for the academic support and development of non-traditional undergraduate medical students. The study was motivated by the need to increase the retention rate of these students. The conceptual framework of this study is based on the theories of Spady, Bean and Tinto. These theories were used to design a retention theory called “Circles of Progression” for non-traditional students in the South African context. As a framework, this theory has guided the empirical investigation and the outcome of this study. The study adopted a case study design to gain an in-depth understanding of the non-traditional undergraduate medical students in the medical school at the University of the Free State. A mixed methods approach was used to conduct the study. Data was collected by means of are a questionnaire and extensive engagement. These methods allowed triangulation and improved the reliability and validity of data and findings. From this study, it became clear that student retention is not due to an isolated factor, but it is a result of a whole range of interrelated factors and therefore there is no one single explanation and solution to student attrition. Based on the literature, generalisations about student retention can be misleading because each country, each institution and each student is unique. South Africa, for instance, cannot be compared to other countries because of its previous political history, its uneven schooling system and the different social backgrounds of the various population xixgroups. Moreover, issues related to retention in the different higher education institutions will not be precisely the same because of different educational systems that existed before political transformation started in 1994. Unfortunately, there is a tendency among both academics and non-academics to provide a single bold answer when asked why students do not perform well. One example of a common answer is that “students do not study”. This answer is often provided without even considering other interrelated factors. The question is “do institutions understand the nature of the problem?” If institutions and the key stakeholders in these institutions could understand the nature of problems faced by non-traditional students, especially undergraduate medical students, they could collaborate, communicate and work together as a team to provide an integrated and holistic programme of action to support and develop these students and therefore, increase their retention rate. The programme of action as proposed in this study could start even before the students enter the university and continue up to their clinical years where they begin to specialise and become professionalised in the medical field.

Die oorhoofste oogmerk van hierdie studie was om ‘n geïntegreerde en holistiese program vir akademiese odersteuning en ontwikkeling van nietradisionele voorgraadse mediese studente te ontwerp. Die studie is gemotiveer deur die behoefte om die retensiekoers van hierdie studente te verhoog. Die konseptuele raamwerk van hierdie studie is gegrond op die teorieë van Spady, Bean en Tinto. Hierdie teorieë is gebruik om ‘n retensieteorie genaamd “Sirkels van Progressie” vir nietradisionele studente in die Suid-Afrikaanse konteks te ontwerp. As ‘n raamwerk het hierdie teorie die empiriese ondersoek en uitkoms van hierdie studie gerig. Die studie het die vorm van ‘n gevallestudie aangeneem ten einde ‘n diepgaande begrip van die nietradisionele voorgraadse mediese studente aan die mediese skool by die Universiteit van die Vrystaat te verkry. Daar is van ‘n gemengdemetodebenadering gebruik gemaak om die studie uit te voer. Die drie data-insamelingsinstrumente wat gebruik is, was ‘n vraelys, omvattende kontak en eweknie-assessering. Hierdie metodes het voorsiening gemaak vir triangulasie en het die betroubaarheid en geldigheid van data en bevindinge verbeter. Uit hierdie studie het duidelik geblyk dat studentretensie nie deur ‘n geïsoleerde faktor teweeg gebring word nie, maar dat dit die gevolg is van ‘n hele reeks verwante faktore. Dus is daar geen enkel verduideliking en oplossing vir studenteverlies nie. Volgens die literatuur kan veralgemenings oor studentretensie misleidend wees omdat elke land, elke instelling en elke student uniek is. Suid-Afrika, byvoorbeeld, kan weens die land se politieke geskiedenis, ongelyke skoolstelsel en die uiteenlopende maatskaplike agtergronde van die verskillende bevolkingsgroepe nie met enige ander lande vergelyk word nie. Daarbenewens sal kwessies wat verband hou met retensie in die verskillende hoëronderwysinstellings nie presies dieselfde wees nie omdat daar verskillende onderwysstelsels bestaan het voordat politieke transformasie in 1994 begin het. Ongelukkig is daar ‘n neiging onder sowel akademici as nie-akademici om ‘n enkele, onomwonde antwoord te gee wanneer gevra word waarom studente nie goed presteer nie. Een voorbeeld van ‘n algemene antwoord is dat studente nie leer nie. Die antwoord word dikwels verskaf sonder om die ander verwante faktore enigsins te oorweeg. Die vraag is, verstaan instellings die aard van die probleem? Indien instellings en die vernaamste aandeelhouers in hierdie instellings die aard van probleme wat nietradisionele studente, en veral voorgraadse mediese studente, in die gesig staar sou kon verstaan, sou hulle as ‘n span kon saamwerk en kommunikeer om ‘n geïntegreerde en holistiese aksieprogram ter ondersteuning en ontwikkeling van hierdie studente te voorsien om sodoende hul retensiekoers te verhoog. Die aksieprogram wat in hierdie studie aan die hand gedoen word sou kon begin nog voordat studente die universiteit betree en voortduur tot in hul kliniese jare waar hulle begin spesialiseer en professionele status in die mediese veld verwerf.
Thesis (Ph.D. (Higher Education Studies))--University of the Free State, 2009
Keywords: Development studies programs -- South Africa -- Bloemfontein; College dropouts -- Prevention; College attendance -- South Africa -- Bloemfontein; Programme of action; Programme; Integrated and holistic approach; Student academic development; Student academic support; Mixed methods research; Academic performance; Non-traditional students; Traditional students; Retention theories; Student dropout; Student attrition; Student retention